2009
DOI: 10.1097/aog.0b013e318188bece
|View full text |Cite
|
Sign up to set email alerts
|

Placenta Percreta Masquerading as an Acute Abdomen

Abstract: The presentation of an acute abdomen with symptoms remote from the site of pathology in the third trimester masked the diagnosis of placenta accreta. When a clear diagnosis cannot be established, operative exploration must be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…One study by Zhang Y, Zhao Y, in 2009 showed spontaneous intra-abdominal bleeding in the third trimester of pregnancy due to a lesion resulting from endometriosis and chronic pelvic inflammatory disease 12 . Other reported causes were placenta percreta 13 , spontaneous rupture of uterine vessels 14,15 , spontaneous rupture of varicose veins on the surface of the uterus 16 spontaneous rupture of a previously unknown scarred uterus 17 or could be idiopathic 18 .…”
Section: Discussionmentioning
confidence: 99%
“…One study by Zhang Y, Zhao Y, in 2009 showed spontaneous intra-abdominal bleeding in the third trimester of pregnancy due to a lesion resulting from endometriosis and chronic pelvic inflammatory disease 12 . Other reported causes were placenta percreta 13 , spontaneous rupture of uterine vessels 14,15 , spontaneous rupture of varicose veins on the surface of the uterus 16 spontaneous rupture of a previously unknown scarred uterus 17 or could be idiopathic 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Anterior placenta praevia in a woman with a previous caesarean section scar increases the risk of morbidly adherent placenta (placenta accreta, increta and percreta) and may result in postpartum haemorrhage. Recently, placenta percreta presenting with an acute abdomen and massive haemoperitoneum in the antepartum period has been reported [14].…”
Section: Management Of Placenta Praeviamentioning
confidence: 99%
“…Although early diagnosis of PAS is desirable to avoid associated adverse outcome [8][9][10][11][12][13][14][15] , it is challenging, and the diagnosis is often missed even in high-risk populations 16 . Among women with anterior placenta previa and previous CS, 1 in 3 is at risk of PAS 17 .…”
Section: Introductionmentioning
confidence: 99%